Upaya dalam Peningkatan Kompetensi Pendidik: Studi pada Dayah Darul Huda Lueng Angen Kabupaten Aceh Utara - Puspitasari, Maya; Prayogi, Eko; Hasibuan, Nurainun (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This research aimed to identify efforts to improve the competence of educators (teungku/guree) at Dayah Darul Huda Lueng Angen, North Aceh Regency. The research method used was a descriptive qualitative approach. Data were obtained through observation, in-depth interviews, and document analysis, which were analyzed through data condensation, data display, and verification/conclusion stages. The results showed that Dayah Darul Huda Lueng Angen plays a strategic role in traditional Islamic education in Aceh but still faces challenges in human resource development, especially in recruitment, competence, and the welfare of its educators. Dayah Darul Huda Lueng Angen has made several efforts to improve the competence of educators, including a program for teaching the "kitab kuning" to ninth-grade students who then become teachers, joint studies between Abu and Ummi to enhance competence, and regular religious guidance. The recommended actions include enhancing the quality of teaching the "kitab kuning," developing training programs and self-development for educators, and providing awards to motivate educators to enhance the quality of education at Dayah Darul Huda Lueng Angen.